2019
DOI: 10.1097/txd.0000000000000930
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Antibiotic Administration as a Potentially Novel Factor Associated With Tacrolimus Trough Variability in Kidney Transplant Recipients: A Preliminary Study

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Several enhanced dosing models have demonstrated improvements in IPV and suggest computer‐assisted dosing, capable of accounting for higher levels of clinical complexity, is another area to target for intervention 75–77 . Further, the understanding of additional sources of tacrolimus variability continues to grow with recent evidence supporting a role for the microbiome and inflammation 78,79 …”
Section: Discussionmentioning
confidence: 99%
“…Several enhanced dosing models have demonstrated improvements in IPV and suggest computer‐assisted dosing, capable of accounting for higher levels of clinical complexity, is another area to target for intervention 75–77 . Further, the understanding of additional sources of tacrolimus variability continues to grow with recent evidence supporting a role for the microbiome and inflammation 78,79 …”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective cohort study of 260 kidney transplant recipients, our group recently identified that antibiotic administration is associated with tacrolimus trough variability, thus indirectly supporting a potential role of the gut microbiota on tacrolimus trough variability. 6 …”
mentioning
confidence: 99%
“…While clinical reports have described important variations in TAC blood levels after ATB [ 22 , 23 ], TAC high intra-individual variability has been identified as a risk factor for the graft outcome [ 4 , 11 ]. Importantly, the above-mentioned TAC PK fluctuations observed under antibiotherapy could not be attributed to direct drug-drug interactions (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Additional lines of evidence support our hypothesis of the existence and the likely importance of an interaction between immunosuppressive therapy and the gut microbiota. Indeed, case reports described alteration in TAC blood concentrations after diarrhoea episodes [ 20 , 21 ] or even antibiotherapy [ 22 , 23 ]. Moreover, a clinical pilot study showed that TAC dose escalation during the first month after transplantation was correlated with the initial abundance of the bacterium Faecalibacterium prausnitzii [ 24 ].…”
Section: Introductionmentioning
confidence: 99%